Nutritional outcomes in HIV-Exposed Infants in the Mingha Program, Dschang-Cameroon (2003-2011) - Sanou Sobze Martin; Djeunang Dongho Ghyslaine Bruna; Russo Gianluca; Zefack Yannick; Sali Ben Bechir Adogaye; Tsi Kien-Atsu; Fotso Jimmy Roger; Tiotsia Tsapi Armand; Ercoli Lucia; Colizzi Vittorio; Zambou Ngoufack Francois (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Background: Prevention of Mother to Child Transmission (PMTCT) is a set of interventions that contribute in reducing the risk of HIV transmission from mother (parents) to the child. The infant feeding choice in the HIV context remains a key item of PMTCT. This study aimed at evaluating the nutritional status of children followed by the Mingha / PMTCT program in the Dschang Health District (DHD) during 09 years of activities. We used a descriptive study based on retrospective data from an intervention conducted at the DHD between 2003 and 2011 on a group of mother-child pairs in the PMTCT (Mingha/PMTCT) facilitation program. The intervention was the formula feeding given to the children from birth till 18 months. The data collected was analyzed using SPSS Version 18 software. Results: Among 328 children accessed, we had a sex ratio of 0.83 with more boys than girls. Severe wasting was found only within 11 boys (3.26%) and only <6 months old children were concerned.Moderate wasting was found among 6 girls (1.74%) and 5 boys (1.52%) and <6 months old children were highly concerned 10 (3.17%). Overweight (3.26%) was highly predominant among 8 boys (2.24%) and except those of <6 months, all the other age groups were concerned. There were no cases of obesity or stunting. Conclusions: The nutritional status of the Mingha/PMTCT program children was quite satisfactory. It characterizes the hope for a suitable nutritional follow up of children in HIV context.Therefore programs like Mingha/PMTCT should be promoted and transferred to other Health Districts and even resource-limited Countries.